Patterns of phenotypic covariation and correlation in modern humans as viewed from morphological integration - González José, Rolando (2003)
Proportionality of phenotypic and genetic distance is of crucial importance to adequately focus on population history and structure, and depends on proportionality of genetic and phenotypic covariance. Constancy of phenotypic covariances is unlikely without constancy of genetic covariation if the later is a substantial component of the former. If phenotypic patterns are found to be relatively stable, the most probable explanation is that genetic covariance matrices are also stable.  Factors like morphological integration account for such stability. Morphological integration can be studied by analyzing the relationships among morphological traits.  We present here a comparison of phenotypic correlation and covariance structure among worldwide human populations. Correlation and covariance matrices between 47 cranial traits were obtained for 28 populations, and compared with design matrices representing functional and developmental constraints. Among-population differences in patterns of correlation and covariation were tested for association with matrices of genetic distances (obtained after an examination of 10 ALU-insertions) and with Mahalanobis distances (computed after cranial traits). All matrix correlations were estimated by means of Mantel tests. Results indicate that correlation and covariance structure in our species is stable and that among-group correlation/covariance similarity is not related with genetic or phenotypic distance. Conversely, genetic and morphological distance matrices were highly correlated. Correlation and covariation patterns were largely associated with functional and developmental factors, which probably account for the stability of covariance patterns.